(untitled) - Muir, John (Washington, D.C, 2001)
Machine generated contents note: CHAPTER I -- Preparing for the Last Journey: -- California, New York, and Boston -- (26January 19ii - z2 August Ig) 3 -- CHAPTER 2 -- Southbound and up the Great Amazon -- (2 August 9I - 25 September 9)35 -- CHAPTER 3 -- Coastal Brazil and up the Iguacu River -- into the Araucaria braziliensis Forests -- (26 September9 - 8 NovemberIg) 69 -- CHAPTER 4 -- Southern Brazil, Uruguay, Argentina, Chile, -- and into the Araucaria imbricata Forests of the Andes -- (9 November gI9i- io DecemberIg)o2 -- CHAPTER 5 -- At Sea, South Africa, the Zambezi River, -- and to the Baobab Trees -- (II December 191 - 6 February i912)127 -- CHAPTER 6 -- East Africa, Lake Victoria, the Headwaters of the Nile, -- and Homeward Bound -- (7 February 192 - 27 March i912)161 -- CHAPTER 7 -- Home to America, California, and Writing: -- The Fate of John Muir and His South America -- and Africa Journals -- (28 March 1912 - 29 December 1912)184 -- APPENDICES -- Appendix A: Timeline/Locator225 -- Appendix B: EditorialMethods239 -- Appendix C: John Muir's Reading and Botanical Notes251 -- Appendix D: SouthAmerica andAfrica Books Owned by Muir267 -- Appendix E:Annotated List of SelectedArchivalMaterials269 -- Appendix F. Table ofEmendations287 -- Notes to Editors Introductions293 -- TextualNotes299 -- Bibliography33 -- Acknowledgments317 -- Credits 321 -- Index323.
Keywords: Natural history,Natural history,Lịch sử về tự nhiên,Lịch sử về tự nhiên; South America,Africa,Miền Nam Hoa Kỳ,Châu Phi